Software-Defined Radio-Based Internet of Things Communication Systems: An Application for the DASH7 Alliance Protocol - Dennis Joosens; Noori BniLam; Rafael Berkvens; Maarten Weyn (Applied Sciences)
Software-Defined Radio (SDR) technology has been a very popular and powerful prototyping device for decades. It finds applications in both fundamental research or application-oriented tasks. Additionally, the continuing rise of the Internet of Things (IoT) necessitates the validation, processing, and decoding of a large number of received signals. This is where SDRs can be a valuable instrument. In this work, we present an open-source software system using GNU Radio and SDRs, which improves the comprehension of the physical layer aspects of Internet of Things communication systems. Our implementation is generic and application-agnostic. Therefore, it can serve as a learning and investigation instrument for any IoT communication system. Within this work, we implement the open-source DASH7 Alliance Protocol (D7AP). The developed software tool can simulate synthetic DASH7 signals, process recorded data sets, and decode the received DASH7 packets in real time using an SDR front-end. The software is accompanied by three data sets collected in controlled, indoor, and suburban environments. The experimental results revealed that the total packet losses of the data sets were 0%, 2.33%, and 16.67%, respectively. Simultaneously, the three data sets were received by a dedicated DASH7 gateway with total packet losses of 0%, 3.83%, and 7.92%, respectively.